Antecedents for the Success of the Adoption of Organizational ERP Among Higher Education Institutions and Competitive Advantage in Egypt - Mohamed, Soliman; Karia, Noorliza (Engineering, Technology and Applied Science Research (ETASR), 2017)
Although the Enterprise Resource Planning (ERP) system has long been acknowledged in higher education institutions (HEIs) to improve their performance and efficiency, there are not many HEIs in Egypt that adopt ERP system and those that do are in an early stage. The research on ERP system in HEI is still limited and in the immature stage, hence little is known about the success factors for the adoption stage of ERP systems. Consequently, this article aims to understand what are the success factors for ERP adoption and further develop a conceptual model that explains the successful implementation of ERP in HEIs and its impact on competitive advantage. Based on previous studies, this paper identifies and conceptualizes success factors for ERP and further develops the proposed model for the adoption of ERP system in HEIs. This article contributes to the development of the theoretical framework of the successful implementation of the ERP system to explain the competitive advantage of HEI by merging information system (IS) success and diffusion of innovation (DOI) theories with the success factors for the adoption stage of ERP systems. The current study will provide recommendations and guidelines for both the potential adopters and the vendors on the successful ERP system adoption.